Efficacy of combined naikan and morita therapies on psychological distress and posttraumatic growth in Chinese patients with advanced cancer: A randomized controlled trial. Issue 30 (30th July 2021) - Han, Xiang-Bei; Fang, Yan-Qiu; Liu, Shu-Xiang; Tan, Yan; Hou, Jun-Jie; Zhao, Li-Jing; Li, Feng
Abstract: Background: Advanced cancer (AC) patients experience serious physical and psychological problems with the disease progression. When approaching the end of life, these patients have to cope with not only the bodily illness, but also the spiritual crisis. Conventional psychological treatments reduce distress to a certain extent, but for patients with AC, especially when they face progressive illness and are approaching death, their psychological problems are complex, and no simple solutions are in sight. Therefore, we designed this study to evaluate the efficacy of the combined Naikan therapy (NT) and Morita therapy (MT) on psychological distress and posttraumatic growth in patients with AC. Method: One hundred thirty patients newly diagnosed with AC were allocated randomly into treatment (n = 65) and control (n = 65) groups. Patients in the treatment group received combined NT and MT for 7 consecutive weeks, while the control group received normal medical treatments without NT and MT. Patients were assessed before and after the therapies. The primary outcome measures include distress thermometer (DT) and posttraumatic growth, and the secondary outcome measure contains the list of distress problems. Results: At the post-treatment stage, the treatment group displayed a decreased score of psychological distress as compared to that in the control group, which accompanied by a higher post-traumatic growth total score and subscale scores in relationship to others, new possibilities, personal strength, spiritual changes, and appreciation of life. A significant decrease in fear, sleeping difficulty/insomnia, nervousness/anxiety, and loss of appetite was also observed in the treatment group. Conclusion: The results proved that the combined Naikan and Morita therapies decreased the psychological distress and improved the posttraumatic growth of the patients with AC. Trial Registration: ChiCTR1900026691. Abstract : Supplemental Digital Content is available in the text